Common Problems Associated with Teeth and Gums: A Review - Jayshree Aate; Satish B. Kosalge; Shubhangi Kambale; Shirin Hanfi; Shreyas Kambgouniwar; Akash Gujarkar; Tejal kale (International Journal of Scientific Research and Innovative Studies, 2022)
Oral health, general symptoms of dental issues, and common dental problems. It also examines how to prevent dental problems, how to maintain good oral health, and when to see a dentist. Oral health is the overall health of the teeth, gums, and mouth. People typically use the term “dental problems” to refer to conditions that affect oral health. Dental problems include cavities, tooth erosion, gum infections, and gum diseases. They can cause pain and discomfort, may affect a person’s ability to eat, and may have a negative impact on an individual’s self-esteem. In most low and middle income countries, the prevalence of oral diseases continues to increase with growing urbanization and changes in living conditions. This is primarily due to inadequate exposure to fluoride (in the water supply and oral hygiene products such as toothpaste), availability and affordability of food with high sugar content and poor access to oral health care services in the community. Marketing of food and beverages high in sugar, as well as tobacco and alcohol, have led to a growing consumption of products that contribute to oral health conditions and other non-communicable diseases.